2009
DOI: 10.1186/1472-6904-9-8
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of adverse drug reaction related admissions according to method of detection, admission urgency and medical department specialty

Abstract: Background: Adverse Drug Reactions (ADRs) have been regarded as a major public health problem since they represent a sizable percentage of admissions. Unfortunately, there is a wide variation of ADR related admissions among different studies. The aim of this study was to evaluate the frequency of ADR related admissions and its dependency on reporting and method of detection, urgency of admissions and included medical departments reflecting department/hospital type within one study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
1
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 28 publications
10
63
1
10
Order By: Relevance
“…Moreover, in general, adverse drug reactions are poorly reported [11][12][13]. These results are consistent with those of the current study, as no side effects were observed in our sample of 134 patients.…”
Section: Doi: 107243/2053-5775-1-4supporting
confidence: 83%
“…Moreover, in general, adverse drug reactions are poorly reported [11][12][13]. These results are consistent with those of the current study, as no side effects were observed in our sample of 134 patients.…”
Section: Doi: 107243/2053-5775-1-4supporting
confidence: 83%
“…4 Cerca de 5% das admissões hospitalares deve-se a iatrogenia medicamentosa. [5][6][7] A incidência de eventos adversos varia de acordo com a faixa etária. A proporção de idosos que é admitida a nível hospitalar devido a iatrogenia medicamentosa é superior comparativamente à estimada para os outros doentes adultos e para as crianças (10,7% vs. 6,3% vs. 4,1%, respetivamente).…”
unclassified
“…Higher prevalence of serious ADEs in 20-40 years age group was also seen in a study by Naveen, et al 13 Male preponderance was observed in the present study, (74%) which was much higher as compared to other studies from Miran Brvar et al from Slovenia in which males constituted 57% of the patients with serious ADEs. 14 In the present study, serious ADEs were caused mainly by Anti epileptic drugs (AED) (32%) followed by Anti HIV drugs and Anti tubercular drugs (18% each). This is in contrast with another study by Pirmohamed et al who reported that NSAIDS (29.6%) followed by diuretics (27.3%) were the major causative drugs for serious ADEs.…”
Section: Discussionmentioning
confidence: 99%